Review Bagriy MM, Dibrova VA, Popadynets OG, Grischuk MI, authors; Bagriy MM, Dibrova VA, editors. [Methods of morphological research]. Vinnitsa: New book; 2016. 328 p. Ukrainian. - journal "Morphologia", Editorial office of (Морфологія / Morphologia / Morfologìâ, 2016)
The publication presents methods that allow to study the morphological features of body tissues in the normal and in pathological conditions, which is the basis of the standards of evidence-based medicine.